Facile construction of fluorescent polymeric aggregates with various morphologies by self-assembly of supramolecular amphiphilic graft copolymers1. Issue 28 (28th July 2015) - Ji, Xiaofan; Li, Yang; Wang, Hu; Zhao, Run; Tang, Guping; Huang, Feihe
<x xml:space="preserve">Abstract</x> Facile construction of fluorescent polymeric aggregates with various morphologies was realized by self-assembly of supramolecular amphiphilic graft copolymers.